Yield Potential Of Indonesian Jatropha New Variety (Jet-1 Agribun) Under Rainfed Condition - Dyah Purwati, Rully; Diarini Riajaya, Prima; Garusti, Garusti; Koseki, Keiichi; Herwati, Anik (Publisher Cv. Inara, 2023)
Jet-1 Agribun is one of the Indonesian Jatropha new varieties suitable for rainfed areas with a high yield of dry seed and oil content. The field trial was conducted at Asembagus Experimental Station in Situbondo, East Java from February to December 2019 and aimed to observe the potential of Jatropha Jet-1 Agribun under rainfed conditions. Observation on seed yield and growth components of Jatropha plantation was also made in two and three years old Jet-1 Agribun. Results of the observation showed that Jet-1 Agribun in the first year produced seed 471.8 kg/ha. A two-year-old plant produced a dry seed of 3,958.7 kg/ha. Three-year-old plants after pruning produced dry seed 910.95 kg/ha and 916.04 kg/ha at 1 m x 1 m and 2 m x 2 m, respectively, indicating that wider spacing is more allowable for cropping with food crops until the canopy closes. Development of Jatropha should be integrated with food crops or other crops through intercropping systems, by using the land around the plants until the canopy closes.